2017
DOI: 10.1097/mpg.0000000000001549
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Quality of Life in Pediatric Crohn Disease

Abstract: Objectives For patients with Crohn's disease (CD), symptom reporting may not coincide with disease state; patients in remission may continue to report symptoms and pain, while other patients may be symptom-free despite a flare. This phenomenon has been documented in adults but only recently assessed in pediatric patients. This study assessed the role of pain reporting and disease state in pediatric patients with CD in understanding psychological distress and quality of life. Methods Participants included 116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…This data was corroborated by other studies described in the literature, among them a study carried out with school children without a specific disease 28 and another study that investigated children with Crohn's disease. 29 In both cases, pain had a negative impact on the various dimensions that make up the concept of QL.…”
Section: Discussionmentioning
confidence: 99%
“…This data was corroborated by other studies described in the literature, among them a study carried out with school children without a specific disease 28 and another study that investigated children with Crohn's disease. 29 In both cases, pain had a negative impact on the various dimensions that make up the concept of QL.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological interventions for pediatric pain management exist and trials have demonstrated efficacy for reduction of pain and disability in both disease-related pain and idiopathic pain conditions (10). Given the increased psychological and physical health burden associated with pain in pediatric IBD (2,4,5), an important next step is tailoring these pain management interventions for youth with IBD. The results from this study suggest that adolescent internalizing symptoms and parent behavior may both be important targets.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a common symptom of inflammatory bowel disease, with the majority of patients reporting pain at initial diagnosis and during recurrence (1). Pain is associated with impaired psychological and physical health outcomes and greater healthcare expenses in youth with IBD, over and above the influence of disease severity (2)(3)(4)(5). While medical intervention in pediatric IBD is focused on disease management (i.e., the escalation of pharmacological intervention), there is increasing concern that pain management has been neglected (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory Bowel Disease is an interesting disease model as patients wax and wane between flares (gut inflammation) and remission (no gut inflammation). While many children become symptomatic as their disease flares, some children are asymptomatic while in a disease flare, while others report symptoms during remission [ 13 ]. The biomedical model explains this as follows [ 14 ].…”
Section: Gut Symptoms Are Either In Your Gut or Your Mindmentioning
confidence: 99%